2020
DOI: 10.1111/bcp.14503
|View full text |Cite
|
Sign up to set email alerts
|

Drug–drug and drug–food interactions in an infant with early‐onset SCN2A epilepsy treated with carbamazepine, phenytoin and a ketogenic diet

Abstract: Sodium channel 2 subunit α (SCN2A) mutations cause difficult‐to‐treat early‐onset epilepsy. Effective treatment includes high‐dose phenytoin or carbamazepine ± ketogenic diet (KD). We describe an infant with early‐onset SCN2A‐epilepsy with subtherapeutic carbamazepine concentration during transition from phenytoin treatment to avoid long‐term neurotoxicity. The transition from high‐dose phenytoin (20 mg kg−1 d−1, concentration: ≥20 mg/L) with KD, to carbamazepine (50–75 mg kg−1 d−1, concentration: 9–12 mg/L) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Although studies addressing CBZ serum levels during KDT are scarce, in the available studies, CBZ levels have been reported to decrease with KDT 20–22 . In a recent case report of a neonate with early onset epilepsy ( SCN2A mutation) which was effectively treated with sodium channel blockers (phenytoin and CBZ) together with KDT, the authors reported a 44% decrease in total CBZ concentrations 35 …”
Section: Methodsmentioning
confidence: 99%
“…Although studies addressing CBZ serum levels during KDT are scarce, in the available studies, CBZ levels have been reported to decrease with KDT 20–22 . In a recent case report of a neonate with early onset epilepsy ( SCN2A mutation) which was effectively treated with sodium channel blockers (phenytoin and CBZ) together with KDT, the authors reported a 44% decrease in total CBZ concentrations 35 …”
Section: Methodsmentioning
confidence: 99%
“…A ketogenic diet causes the decrease in the serum concentration of CBZ in young patients (median, 2.91 years), but not significantly [94]. In infants, the ketogenic diet significantly decreased CBZ concentration in 44% during the effective treatment of early onset epilepsy which includes high doses of PHT or CBZ [95].…”
Section: Carbamazepinementioning
confidence: 95%
“…There is a very significant dose-dependency of CYP3A4 induction, resulting in a 3-fold increase in CBZ clearance at high PHT doses of 20 mg/kg/day, which increases the concentration-dependent auto-induction of CBZ clearance (2.5-fold at 12 mg/L) [95]. The clearance of busulfan is altered as result of the interaction with PHT and changes in sub or supra concentrations can cause an increase in toxicity [145].…”
Section: Phenytoin and Phosphenytoinmentioning
confidence: 99%
“…At present, pharmacological treatment with antiepileptic drugs (AEDs) is still a primary selection for most patients. Although the new generation of AEDs has overcome some shortcomings of the "classical" or "first-generation" such as inter-individual variability, narrow therapeutic scopes, nonlinear pharmacokinetics, and serious adverse effects [5,6], however, unpredictable pharmacokinetic interaction of drug-drug or drug-food [7][8][9][10][11] and genetic variation related with drug-metabolizing enzymes or transporters (gene polymorphism) [12] may influence drug serum or plasma concentration, which may further influence drug efficacy or result in adverse effects. In addition, first-generation AEDs such as carbamazepine (CBZ), ethosuximide (ESM), phenobarbital (PHB), phenytoin (PHT), primidone (PRM), and valproic acid are still widely used in primary hospital of China or other developing countries.…”
Section: Introductionmentioning
confidence: 99%